A Reversible Gene-Targeting Strategy Identifies Synthetic Lethal Interactions between MK2 and p53 in the DNA Damage Response In Vivo - Sandra Morandell (Cell Reports, 2013)
A fundamental limitation in devising new therapeutic strategies for killing cancer cells with DNA damaging agents is the need to identify synthetic lethal interactions between tumor-specific mutations and components of the DNA damage response (DDR) in vivo. The stress-activated p38 mitogen-activated protein kinase (MAPK)/MAPKAP kinase-2 (MK2) pathway is a critical component of the DDR network in p53-deficient tumor cells in vitro. To explore the relevance of this pathway for cancer therapy in vivo, we developed a specific gene targeting strategy in which Cre-mediated recombination simultaneously creates isogenic MK2-proficient and MK2-deficient tumors within a single animal. This allows direct identification of MK2 synthetic lethality with mutations that promote tumor development or control response to genotoxic treatment. In an autochthonous model of non-small-cell lung cancer (NSCLC), we demonstrate that MK2 is responsible for resistance of p53-deficient tumors to cisplatin, indicating synthetic lethality between p53 and MK2 can successfully be exploited for enhanced sensitization of tumors to DNA-damaging chemotherapeutics in vivo.